IMPLEMENTATION OF ACADEMIC SUPERVISION IN IMPROVING TEACHERS' PEDAGOGICAL COMPETENCE IN ELEMENTARY SCHOOL - Istikomah Istikomah; Sumarno Sumarno; Rasiman Rasiman (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Academic supervision is a crucial element in school management, focusing on improving the quality of teaching and teachers’ pedagogical competence. This article aims to provide a comprehensive description of the planning, implementation, evaluation, and follow-up processes of academic supervision at SD Negeri 02 Limbangan, Ulujami District, Pemalang Regency. This research employs a qualitative descriptive approach, using data collection techniques such as interviews, observations, and documentation. The results show that supervision planning is conducted cooperatively by involving teachers; the implementation takes place through classroom observations and reflective discussions, while the evaluation is carried out comprehensively by providing constructive feedback. The follow-up includes giving rewards as well as competency development programs through training. These findings highlight the importance of structured academic supervision in promoting teacher professionalism and improving the quality of learning.